Autophagic vacuolar myopathy is a common feature of CLN3 disease. Issue 11 (14th October 2018) - Radke, Josefine; Koll, Randi; Gill, Esther; Wiese, Lars; Schulz, Angela; Kohlschütter, Alfried; Schuelke, Markus; Hagel, Christian; Stenzel, Werner; Goebel, Hans H.
Abstract: Objective: The neuronal ceroid lipofuscinoses (NCL) are genetic degenerative disorders of brain and retina. NCL with juvenile onset (JNCL) is genetically heterogeneous but most frequently caused by mutations of CLN3. Classical juvenile CLN3 includes a rare protracted form, which has previously been linked to autophagic vacuolar myopathy (AVM). Our study investigates the association of AVM with classic, non‐protracted CLN3. Methods: Evaluation of skeletal muscle biopsies from three, non‐related patients with classic, non‐protracted and one patient with protracted CLN3 disease by histology, immunohistochemistry, electron microscopy, and Sanger sequencing of the coding region of the CLN3 gene. Results: We identified a novel heterozygous CLN3 mutation (c.1056+34C>A) in one of our patients with classic, non‐protracted CLN3 disease. The skeletal muscle of all CLN3 patients was homogeneously affected by an AVM characterized by autophagic vacuoles with sarcolemmal features and characteristic lysosomal pathology. Interpretation: Our observations show that AVM is not an exceptional phenomenon restricted to protracted CLN3 but rather a common feature in CLN3 myopathology. Therefore, CLN3 myopathology should be included in the diagnostic spectrum of autophagic vacuolar myopathies.